Earth system dynamics : ESD (Copernicus, 2010)
An international scientific journal dedicated to the publication and public discussion of studies that take an interdisciplinary perspective of the functioning of the whole Earth system and global change.
Keywords: Earth sciences : Periodicals; Global environmental change : Periodicals; Climatic changes : Periodicals; Global environmental change; Climatic changes; Earth sciences